Pengaruh Suhu Media Tanam Terhadap Waktu Perkecambahan Kacang Hijau - Dian Mardhiana; Abdul Hamid; Ahmad Farhan (Prodi Fisika FKIP Unram, 2021)
The research was conducted entitled The Effect of Soil Temperature on Mung Bean Germination Time. This study aims to determine the optimal temperature of the growing media in the germination process of green beans. This study was arranged in a completely randomized design (CRD) with one factor, namely the temperature of the growing media (soil) at the same time consisting of control (30⁰C), 27⁰C, 33⁰C, 36⁰C, 39⁰C. The parameter measured was the germination time of green beans. Variance data were analyzed by DMRT test at level = 5%. The results showed that the temperature of the growing media affected the germination time of green beans. The treatment that caused the optimal germination time was 33⁰C.Keywords: Soil Temperature, Time, mung bean